Pemberdayaan Masyarakat Melalui Pembinaan dan Bantuan Modal Usaha di Utan Kayu Jakarta Timur - Ulza, Emaridial Ulza; Ferdiansyah, Ferdiansyah (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2018)
The opening of a free market that now spans ASEAN and Asia Pacific region becomes a challenge as well as momentum for Indonesia to be able to show its existence in the international world through various fields such as human resources, market share expansion, and others by offering innovative domestic products. This background is the basis of community service. Specifically, the purpose of community service activities are: (1) to prepare entrepreneurs who are ready to compete healthily, (2) to develop micro and small business (UMKM) of society towards better (3) to foster entrepreneurship spirit for society. Methods in the implementation of community service programs include: (1) preparatory stage, ie by consulting with lecturers intensive as well as observing the target community program, and (2) the stage of implementation of activities, that is doing entrepreneurship and skill training. The outputs of community service activities include: (1) improving entrepreneurship for the target group, (2) increasing the economic level of the target group, and (2) the results of activities in the form of published products and having economic value. Outcome obtained from this activity is the development of rice business of one citizen.